1984
DOI: 10.1159/000233447
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Monocytes and Responder Cells in Suppression of Antigen-Specific T Cell Proliferation in Chronic Renal Failure

Abstract: The response of peripheral blood lymphocytes (PBL) to the antigen tetanus toxoid (TT) in patients with chronic renal failure being maintained on hemodialysis was examined. We have found that: (1) the response of patients’ unfractionated PBL to TT is markedly suppressed when compared to the response of control PBL; (2) the response of patients’ purified T cells and T4+ cells to TT co-cultured with 5% autologous monocytes is suppressed when compared to the response of comparable control cultures; (3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

1987
1987
1991
1991

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…In agreement with earlier reports our results show that the proliferative response of both T lymphocytes [19,23,24] and B lymphocytes [30,31] in uremic patients after in vitro stimulations with lectins is significantly reduced. The most prominent defect was seen in T-cell-dependent B lymphocyte proliferation after PWM stimulus.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In agreement with earlier reports our results show that the proliferative response of both T lymphocytes [19,23,24] and B lymphocytes [30,31] in uremic patients after in vitro stimulations with lectins is significantly reduced. The most prominent defect was seen in T-cell-dependent B lymphocyte proliferation after PWM stimulus.…”
Section: Discussionsupporting
confidence: 94%
“…Their delayed hypersensitiv ity reactions to common antigens are low [13], the re sponse to hepatitis B virus infection is altered [14][15][16] and the seroconversion rates to hepatitis B vaccination are low [17,18]. These findings have been associated with change in the number of functional T cell subsets [19][20][21][22], impaired in vitro responses to mitogens [19,[23][24][25], in creased suppressor cell activity [26][27][28][29], defective B cell responses [30,31] and altered monocyte [24,32], natural killer [33,34] or polymorphonuclear cell function [35][36][37], Changes in T cell subsets and cell-mediated immunity observed in earlier studies [19,38] were correlated with the duration of dialysis treatment. Over the last few years a number of studies have focused on the role of interleu kin-2 (IL-2) and its receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Secretion of IL-2 was also completely normal in patients dialyzed with a polysul fone-membrane, while this function has been shown in recent studies to be impaired in patients on cuprophane membrane hemodialysis [14,20]. Previous studies have implied that in hemodialysis patients the impairment of T cell function can be attributed to suppressive effects of monocytes [5,21], In the patients on 'high-flux' dialysis studied here, IL-1 production was comparable to that in controls, suggesting that this function of monocytes was not affected.…”
Section: Discussionmentioning
confidence: 95%
“…6], immunoglobulin production [7. 8], and monocyte activ ity [5] are also significantly impaired. Earlier studies of lymphocyte numbers or their subset proportions have shown that counts of either T or B lymphocytes are often significantly reduced in hemodialyzed patients [9. 10], Significant changes were detected particularly in patients who were hemodialyzed for long time periods [6], Re cently, new hemodialysis membranes have been intro duced which are reported to improve the overall clinical condition of dialyzed patients, mainly by reducing the incidence of complications of hemodialysis such as amy loidosis, carpal tunnel syndrome and joint abnormalities [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…(*4) Παρασκευή διαλύματος α.ΙΝΕ συγκέντρωσης 1000 Ul/ml. Λήψη 1 fi INTRON A με 5x10 6 Ul στα 5ml. Με δύο αραιώσεις, 100 μΙ από το αρχικό σε 10 ml και 1 ml από τη δεύτερη αραίωση σε 9 ml water for injection σε στείρες συνθήκες δημιουργία διαλύματος 10 ml με 1000 Ul/mi και τοποθέτηση του σε -20°C.…”
Section: παρατηρώunclassified